(untitled) (Journal of the College of Basic Education, 2025)
The roots of the conflict between the countries of the Horn of Africa and the countries bordering it lie in the contradictory concepts of national identity and national unity, as well as the attempts of the major powers to dominate its strategic location, exploiting the regional and national contradictions between those countries overlooking the Red Sea and the Indian Ocean. Yemen played a vital and important role in supporting peaceful mediation efforts to enhance stability in the Horn of Africa region, in addition to the political and strategic effects that this conflict had on its regional relations. Although the conflict between Ethiopia and Eritrea ended with the Algiers Agreement, Yemeni efforts through mediation and calling for dialogue and peace between the two sides prevented the expansion of the conflict and were positive, ultimately ending with sitting at the negotiating table and ending that conflict.